The shifting politics of patient activism: From bio-sociality to bio-digital citizenship. (July 2019) - Petersen, Alan; Schermuly, Allegra Clare; Anderson, Alison
Digital media provide novel tools for patient activists from disease- and condition-specific communities. While those with debilitating conditions or disabilities have long recognised the value of collective action for advancing their interests, digital media offer activists unparalleled opportunities to fulfil their goals. This article explores the shifting politics of 'activism' in the increasingly digitally mediated, commercialised context of healthcare, asking: what role have digital media played in the repertoire of activists' strategies? And, to what extent and how has the use of such media impacted the very concept of activism? Building on sociological ideas on emergent forms of 'biological citizenship' and drawing on findings from an analysis of available media, including television and print news reportage, online communications, published histories and campaign material and other information produced by activists in HIV/AIDS and breast cancer communities, we argue that digital media have profoundly shaped how 'activism' is enacted, both the goals pursued and the strategies adopted, which serve to broadly align contemporary patient communities' interests with those of science and business. This alignment, which we characterise as 'bio-digital citizenship', has involved a fundamental reorientation of 'activism' from less of a struggle for rights to more of a striving to achieve a public profile and attract funding. We conclude by calling for a reconceptualisation of 'activism' to more adequately reflect the workings of power in the digital age, whereby the agency and hopes of citizens are central to the workings of political rule.